A psicologia do ego de ernst kris e seu legado para a psicanálise da arte - Dionisio, Gustavo Henrique [UNESP] (FapUNIFESP (SciELO), 2012)
This article intends to discuss the importance of the ego-psychology towards the psychoanalytical interpretation of the aesthetic experience. Its focus is based on the Ernst Kris original work, therefore it intends to present certain basis of his aesthetical thinking. In this case, however, it will suggest one certain reading which emphasizes the problem of sublimation as a drive destination-and not as a defense mechanism-in within this relationship between art and psychoanalysis; hence, it brings out a phenomenon that crosses the psychoanalytical thinking since its first conception.
Ernst Kris ego-psychology and its legacy to the psychoanalysis of art
Keywords: Aesthetics; Ego-psychology; Metapsychology; Psychoanalysis